2005
DOI: 10.1002/chem.200401279
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Nondecarbonylative Addition Reaction of ClCOCOOC2H5 to Alkynes

Abstract: Addition of ethoxalyl chloride (ClCOCOOEt) to terminal alkynes at 60 degrees C in the presence of a rhodium(I)-phosphine complex catalyst chosen from a wide range affords 4-chloro-2-oxo-3-alkenoates regio- and stereoselectively. Functional groups such as chloro, cyano, alkoxy, siloxy, and hydroxy are tolerated. The oxidative addition of ethoxalyl chloride to [RhCl(CO)(PR(3))(2)] proceeds readily at 60 degrees C or room temperature and gives [RhCl(2)(COCOOEt)(CO)(PR(3))(2)] (PR(3) = PPh(2)Me, PPhMe(2), PMe(3)) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 60 publications
2
16
0
3
Order By: Relevance
“…Rhodium catalyzed the addition of ethoxallylchloride (Eq. (129)) [804] and of perfluorinated acid chlorides [805] to alkynes. Nickel catalyzed an alkylative carboxylation of alkynes using organozinc reagents and carbon dioxide (Eq.…”
Section: Formation Of Carbon-carbon Bonds From Alkene and Alkynesmentioning
confidence: 99%
“…Rhodium catalyzed the addition of ethoxallylchloride (Eq. (129)) [804] and of perfluorinated acid chlorides [805] to alkynes. Nickel catalyzed an alkylative carboxylation of alkynes using organozinc reagents and carbon dioxide (Eq.…”
Section: Formation Of Carbon-carbon Bonds From Alkene and Alkynesmentioning
confidence: 99%
“…Rhodium complexes are versatile catalysts and can be used for several organic reactions, like oxidation [40], reduction [41], carbonylation [42], addition [43], hydroformylation [44], hydroboration [45] etc. The Wilkinson catalyst, RhCl(PPh 3 ) 3 is the classic example of a homogeneous hydrogenation catalyst [46].…”
Section: Introductionmentioning
confidence: 99%
“…Tanaka and co-workers showed that such reactions proceed with the retention of CO in the presence of the same catalyst when chloroformate esters, which are particularly electron-poor substrates, are used. [8] Over the following years, the Tanaka research group developed tailored procedures for the stereoselective, CO-retentive addition of ethoxalyl chloride, [9] perfluorinated acid chlorides, [10] and chloroacetyl chlorides [11] (Scheme 2, bottom).…”
mentioning
confidence: 99%